2022
DOI: 10.1021/acsami.2c04408
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity and Schottky Heterojunction Engineering in AgNbO3: A Simultaneous Way of Boosting Piezo-photocatalytic Activity

Abstract: As an efficient and economical way of dealing with organic pollutants, piezo-photocatalysis has attracted great interest. In this work, we demonstrated that ferroelectricity and Schottky heterojunction engineering could significantly enhance the piezo-photocatalytic activity of AgNbO3. The poled 20 mol % K+ doped AgNbO3 disclosed its superior piezo-photocatalytic activity of 0.131 min–1 for 10 mg·L–1 RhB, which is 7.8 times of the pristine one under the condition of illumination only. The designed piezo-photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…For direct band gap semiconductors, n is equal to 1, whereas for indirect band gap semiconductors, n is equal to 4. AgNbO 3 37 and CuBi 2 O 4 51 are considered as direct band gap semiconductors. Therefore, according to the (αhv) 2 −hv curves of the samples (Figure 5b), the obtained optical band gaps of AgNbO 3 and CuBi 2 O 4 were 2.81 and 1.82 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For direct band gap semiconductors, n is equal to 1, whereas for indirect band gap semiconductors, n is equal to 4. AgNbO 3 37 and CuBi 2 O 4 51 are considered as direct band gap semiconductors. Therefore, according to the (αhv) 2 −hv curves of the samples (Figure 5b), the obtained optical band gaps of AgNbO 3 and CuBi 2 O 4 were 2.81 and 1.82 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the depolarization electric field originating from the spontaneous polarization of ferroelectrics and the piezoelectric potential generated under stress in ferro-/piezoelectric materials with the piezoelectric effect are also used as the built-in electric field to suppress the recombination of photoinduced carriers in the photocatalyst. Ferroelectric materials with the depolarization electric field and piezoelectric potential have been widely used to boost photocatalytic efficiency. AgNbO 3 as an antiferroelectric material with a piezoelectric coefficient of 330 pC/N exhibits a stronger piezoelectric response, and enhances the photocatalytic performances of AgNbO 3 by regulating its ferro-/piezoelectric characteristics has been proved to be an important strategy. However, the limited visible light absorption ability of AgNbO 3 with a wider band gap (∼2.8 eV) hinders further improvement of its photocatalytic degradation performance. Constructing AgNbO 3 and the semiconductor with a narrower band gap to be a heterojunction is a simple and effective strategy to enhance its visible light absorption ability, and this heterojunction photocatalyst with suitable energy band matching is expected to achieve enhanced carrier separation ability.…”
Section: Introductionmentioning
confidence: 99%
“…17 Luo et al reported Ag nanoparticle/K + doped AgNbO 3 Schottky heterojunctions, which revealed an improved separation efficiency of electrons and holes and demonstrated outstanding piezo-photocatalytic activities in pollution degradation. 18 Recently, direct Z scheme heterostructures have begun to receive increasing attention in photocatalytic fields due to the improved separation efficiency of carriers and simultaneously maximized redox capability. 14 After the formation of direct Z scheme heterostructures, the photogenerated electrons and holes can be enriched on the semiconductor with a higher reduction and oxidation ability, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The piezo-photocatalytic activity of the poled Ag/Ag 0.8 K 0.2 NbO 3 Schottky heterojunction for RhB was 7.8 times of the pristine AgNbO 3 under only illumination. [25] The formation of the interfacial electric field can be accelerated by constructing the Ag 2 O/AgNbO 3 p-n heterojunction, which enhances the separation of photogenerated electron-hole pairs, resulting in a high degradation rate of 95.4 % within 90 minutes for RhB. [26] Some metal cations (such as Bi 3 + , [27] La 3 + [15] at A sites, and Zr 4 + [28,29] at B sites) and LiTaO 3 [30] were introduced into AgNbO 3 to improve its photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%